(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2021)
Present paper outlines the advantages of experiments performed using human body part surrogates (physical models) in combination with virtual experiments carried out using numerical models for the medical studies, safety research and development of safety equipment. Material uses the examples of setups using instrumented human head and neck surrogates developed and constructed at Mid Sweden University, Sweden and the University of Padua, Italy.